Pendampingan UMK Kedai Kuliner Berbasis Model Partisipatif untuk Sertifikasi Halal Self-Declare di Kota Bandung - Muljana, Fathan Hadinur Malik; Najmudin, Deden; Faruq, Raffi Muhammad; Fahrezi, Reza (Penerbit Widina, Widina Media Utama, 2025)
The self-declare halal certification introduced under BPJPH Decree No. 146 of 2025 has opened new opportunities for micro and small enterprises (MSEs), particularly meat-based culinary businesses that face the most complex halal critical points. Indonesia, with over 65 million MSMEs, still struggles with limited halal literacy, challenges in verifying critical ingredients, and incomplete Halal Product Assurance System (SJPH) documentation. This community engagement project was conducted with a single SME, Dapur Mamih in East Bandung, aiming to strengthen SJPH understanding, improve ingredient traceability, ensure proper documentation, and build the capacity to input applications through the Sihalal platform until the halal certificate was issued. Using a Participatory Action Research (PAR) approach, the program involved field observation, interviews, intensive mentoring, and document verification over one month (August 2025). The pre- and post-test questionnaires revealed clear improvements: halal literacy increased from 35% to 75%, ingredient record-keeping from 40% to 68%, and document validation from 30% to 85%. The SME responded positively, demonstrating behavioral changes in ingredient selection, consistency in record-keeping, and successful submission of data through Sihalal, which led to halal certification of seven culinary menus by BPJPH. These results confirm that participatory mentoring not only enhances declarative knowledge but also develops technical skills, thereby achieving the program’s goal of preparing SMEs for halal self-declare certification. ABSTRAKSertifikasi halal self-declare melalui Keputusan Kepala BPJPH No. 146 Tahun 2025 membuka peluang besar bagi usaha mikro dan kecil (UMK), khususnya kuliner berbahan daging yang memiliki titik kritis paling kompleks. Indonesia dengan lebih dari 65 juta UMKM masih menghadapi tantangan literasi halal yang rendah, keterbatasan verifikasi bahan, dan ketidaktertiban dokumen Sistem Jaminan Produk Halal (SJPH). Kegiatan pengabdian ini dilakukan pada satu UMK, yaitu Dapur Mamih di Bandung Timur, dengan tujuan meningkatkan pemahaman SJPH, keterlacakan bahan, kelengkapan dokumen, serta kemampuan menginput data ajuan pada aplikasi Sihalal hingga terbit sertifikat halal. Pendekatan Participatory Action Research (PAR) diterapkan melalui observasi, wawancara, pendampingan intensif, dan verifikasi dokumen selama satu bulan (Agustus 2025). Hasil kuisioner pre-test dan post-test menunjukkan peningkatan: literasi halal naik dari 35% menjadi 75%, pencatatan bahan dari 40% menjadi 68%, dan validasi dokumen dari 30% menjadi 85%. Respon pelaku usaha positif, ditandai dengan perubahan perilaku dalam pemilihan bahan, keteraturan pencatatan, serta keberhasilan menginput data ke Sihalal hingga tujuh menu kuliner memperoleh sertifikat halal BPJPH. Dengan demikian, pendampingan partisipatif berbasis PAR tidak hanya meningkatkan pengetahuan deklaratif, tetapi juga membangun keterampilan teknis, sehingga tujuan pengabdian tercapai dalam memperkuat kesiapan UMK menghadapi sertifikasi halal self-declare.